Interview with Prof. Jan Kubik: The FATIGUE Project - Jan Kubik (Slovo, 2017)
SCIENTIST-IN-CHARGE AND MANAGING DIRECTOR OF THE FATIGUE PROJECT, PROFESSOR JAN KUBIK, IN CONVERSATION WITH SLOVO’S EXECUTIVE EDITOR BORIMIR TOTEV. Prof. Jan Kubik was the Director of the School of Slavonic and East European Studies between January 2015 and August 2017, as well as Pro-Vice Provost for Europe at University College London. Kubik works on the interplay between power (politics) and culture, protest politics and social movements, and post-communist transformations. He also writes about qualitative methods in the social sciences. His first and one of the most recent books, ‘The Power of Symbols against the Symbols of Power’ (Penn State Press) and ‘Anthropology and Political Science’ (Berghahn, with Myron Aronoff) are the best exemplifications of his approach. Kubik studies politics and culture comparatively, but the principal source of his observations and data are Poland and East Central Europe. Since 1991 he has taught in the Department of Political Science at Rutgers University, where he once served as the Chair. He has lectured around the world and has held several prestigious teaching posts and fellowships, including the Graduate School of Social Sciences, Polish Academy of Sciences. Read full text here.